Sex education of adolescents with autism spectrum disorders in Poland - GULCZYŃSKA, ANNA; WOJCIECHOWSKA, ANETA (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
Anna Gulczyńska, Aneta Wojciechowska, Sex education of adolescents with autism spectrum disorders in Poland. Interdisciplinary Contexts of Special Pedagogy, no. 24, Poznań 2019. Pp. 155-176. Adam Mickiewicz University Press. ISSN 2300-391X.DOI: https://doi.org/10.14746/ikps.2019.24.09 The aim of this article is to present the results of research into how mothers of individuals with ASD perceive school sex education. The article aims to contribute to the discussion on the need to introduce changes in the Polish education system as far as the area of sexuality is concerned. The study was carried out in two parts, at time intervals. The results were obtained only from mothers, which corresponds with the conclusion that mothers talk about matters of sexuality more often than fathers do and with daughters rather than with sons. The results indicate that mothers want to influence the sex education of their children, at the same time having no knowledge of what topics they are pursuing or can pursue with their child during formal sex education at school (education for living in a family).